Mitigation of Ochratoxin A-Induced Renal Toxicity by Kaempferol in Albino Mice - Norah Fahad Saad Bosaad; Peramaiyan Rajendran*; Rebai Ben Ammar; Gamal Mahmoud Bekhet; Mohammed Salem Moqbel; Saeed Yaseen Al-Ramadan; Hamad Abu Zahra (Iranian Society of Pharmacognosy, 2024)
Background and objective: This study investigated the protective effects of kaempferol, a natural flavonoid known for its antioxidant properties, against ochratoxin A-induced renal damage. Ochratoxin A, a nephrotoxic mycotoxin found in contaminated food and feed, primarily induces renal damage through oxidative stress. The objective was to assess kaempferol's potential in mitigating ochratoxin A -induced renal toxicity and its underlying molecular mechanisms. Methods: Male albino mice were divided into four groups: normal control, kaempferol control, ochratoxin A -induced renal toxicity, and ochratoxin A -induced renal toxicity treated with kaempferol. Ochratoxin A was administered twice a week for 8 weeks at 5 mg/kg body weight to induce renal toxicity. Kaempferol (50 mg/kg) was administered twice a week for 8 weeks after a 4-hour interval following ochratoxin A administration. Results: Results showed that kaempferol normalized levels of blood urea nitrogen (BUN) and creatinine, indicating protection against ochratoxin A-induced pathophysiology. Kaempferol also increased phosphorylation of PI3K and AKT, potentially activating antioxidative and anti-apoptotic signaling pathways regulated by Nrf2. Additionally, kaempferol enhanced Bcl-2 activation while suppressing caspase-3, suggesting anti-apoptotic effects. Histopathological analysis revealed reduced renal damage in kaempferol-treated mice compared to those exposed to ochratoxin A alone. Conclusion: Kaempferol demonstrated efficacy in preventing ochratoxin A -induced kidney injury through antioxidative and anti-apoptotic mechanisms. These findings suggest potential therapeutic applications of kaempferol in oxidative stress-induced renal damage.